Legalitas Nikah Sirrî Ditinjau Dari Kaidah Fikih - Muhammadi, Fauzan (Fakultas Syariah, 2017)
Unrecorded marriage becomes legal issues in Indonesia after the government has obliged that marriage must be registered with the Registrar of Marriage Officers or the Office of Religious Affairs. The propnents of this marriage maintain that such marriage is considered valid and legal under Islamic law, although it is not admitted by the state law. The objective of this research is to discuss the legal problems of unrecorded marriage in Islamic law in the Indonesian context and to understand the changes of legal status of unrecorded marriage from the perspective of Islamic legal maxim. The methodology used in this research is descriptive-qualitative analysis. This study shows that according to the perspective of Islamic legal maxim, unrecorded marriage is not restricted but it may fall under the category of forbidden. It is because there are many deviations in a marriage when it is not registered. Thus, this could harm the family lived in the future.Pasca pemerintah mengeluarkan kebijakan untuk mewajibkan pencatatan nikah di hadapan Kantor Urusan Agama (KUA)/Petugas Pencatat Nikah (PPN), nikah Sirrî menjadi isu hukum yang hangat di Indonesia. Permasalahan ini muncul sebagai bagian dari pemahaman masyarakat bahwa pernikahan mereka dianggap valid dan sah secara agama (hukum Islam) namun ‘illegal’ secara hukum positif. Studi ini berusaha untuk mendiskusikan legalitas nikah sirrî dalam hukum islam di Indonesia sekaligus untuk memahami probabilitas perubahan hukum nikah sirrî melalui Kaidah Fikih. Penelitian ini menggunakan analisa deskriptif-kualitatif melalui studi literatur. Hasil dari studi ini adalah dimungkinkannya perubahan hukum nikah sirrî dari yang sebelumnya boleh menjadi haram. Ini berdasarkan fakta banyaknya penyimpangan wewenang pernikahan yang tidak tercatat yang merugikan kehidupan keluarga di masa yang akan datang.